Asian Sand Dust Particles Increased Pneumococcal Biofilm Formation in vitro and Colonization in Human Middle Ear Epithelial Cells and Rat Middle Ear Mucosa - Yadav, Mukesh Kumar; Go, Yoon Young; Chae, Sung-Won; Park, Moo Kyun; Song, Jae-Jun (Frontiers in Genetics, 2020)
Introduction:Air pollutants such as Asian sand dust (ASD) and Streptococcus pneumoniae are risk factor for OM. In this study we evaluate the role of ASD in pneumococcal in vitro biofilm growth and colonization on HMEECs and rat middle ear using rat OM model. Methods: S. pneumoniae D39 in vitro biofilms growth in the presence of ASD (50-300 µg/mL), was evaluated in metal ion-free BHI medium using CV-microplate assay, cfu counts, resazurin staining, scanning electron microscopy (SEM) and confocal microscopy (CF). Biofilm gene expression analysis was performed using real-time RT-PCR. The effects of ASD or S. pneumoniae individually or on co-treatment on HMEECs were evaluated by detecting HMEEC viability, apoptosis, and reactive oxygen species (ROS) production. In vivo colonization of S. pneumoniae in the presence of ASD was evaluated using rat OM model, and RNA-Seq was used to evaluate the alterations in gene expression in rat middle ear mucosa. Results:S. pneumoniae biofilm growth was significantly (P<0.05) elevated in the presence of ASD. SEM and CF analysis revealed thick and organized pneumococcal biofilms in presence of ASD (300 µg/mL). However, in the absence of ASD, bacteria were unable to form organized biofilms, the cell size was smaller than normal, and long chain-like structures were formed. Biofilms grown in the presence of ASD showed elevated expression levels of genes involved in biofilm formation (luxS), competence (comA, comB, ciaR), and toxin production (lytA and ply). Prior exposure of HMEECs to ASD, followed by treatment for pneumococci, significantly (P<0.05) decreased cell viability and increased apoptosis, and ROS production. In vivo experiment results showed significantly (P<0.05) more than 65% increased bacteria colonization in rat middle ear mucosa in presence of ASD. The apoptosis, cell death, DNA repair, inflammation and immune response were differentially regulated in three treatments, however number of genes expressed in co-treatments were higher than single treatment. In co-treatment antimicrobial protein/peptides related genes (S100A family, Np4, DEFB family, RATNP-3B), OM related genes (CYLD, SMAD, FBXO11, CD14) were down regulated, and inflammatory cytokines and interleukins such as IL1β, TNF related genes expression were elevated. Conclusion: ASD presence increased the generation of pneumococcal biofilms and colonization